Occupational accidents in mining workers: scoping review of studies published in the last 13 years - Liliana Cruz-Ausejo; Nieves Alejandra Cama-Ttito; Patricia Flores Solano; Anthony Copez-Lonzoy; Víctor Juan Vera-Ponce (BMJ Open, 2024)
Objective Mining activity represents one of the most hazardous occupations related to health, with 8% of fatal injuries concentrated in this sector worldwide. Thus, it is crucial to timely identify the factors involved in such injuries. We aimed to explore the sociodemographic and occupational/organisational factors associated with injuries, causative agents and subsequent disabilities and fatality of workers exposed to occupational injuries in the mining sector.Design A secondary scoping review was conducted following the Joanna Briggs Institute guidelines.Data sources Scopus, Embase, Virtual Health Library, SciELO and PubMed databases were searched in February 2022 and updated in October 2023. The protocol was developed in April 2022.Eligibility criteria for selecting studies We included observational studies published within the last 13 years (2010–2022) which provided information on injuries of the mining workers and reported associated factors as well as health consequences.Data extraction and synthesis Two independent reviewers examined the eligibility criteria, screened and coded the extracted information using prevalidated data extraction tools, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses—Extension for Scoping Reviews reporting guidelines.Results A total of 123 studies were found, of which nine were selected for inclusion in this review. Participants were between 15 and 80 years old, and the rate of injuries ranged from 4.4% to 10.6% of reported cases. Among the total selected studies, mechanical agents were identified as the leading cause of injuries in six studies. The factors associated with injuries included age, gender (female) and biochemical characteristics. On the other hand, occupational and organisational factors encompassed work shift, outsourcing (contractors) and less than 2 years of experience in the sector.Conclusion This review emphasises that both work-related and individual characteristics are significantly related factors of injuries. Moreover, commonly reported health consequences of injuries encompass mortality, average days lost and permanent, partial or total disability.